2021
DOI: 10.1049/htl2.12008
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring data integrity of healthcare information in the era of digital health

Abstract: Data integrity continues to be a persistent problem in the current healthcare sector. It ensures that the data is correct and has not even in any manner been improperly changed. Incorrect data might become significant health threats for patients and a big responsibility for clinicians, resulting in problems such as scam, misconduct, inadequate treatment and data theft. This sort of endangering scenario causes tremendous difficulty in handling healthcare data. This research intends to describe the threat plot o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Another research intends to describe the threat plot of data integrity in healthcare through numerous attack statistics from around the world and Saudi Arabia and identify the criticality in Saudi Arabia in particular. The results of this SLR conducted by Mohammad et al [9] strongly indicate that the healthcare sector needs a new and more robust data integrity approach.…”
Section: Related Workmentioning
confidence: 88%
“…Another research intends to describe the threat plot of data integrity in healthcare through numerous attack statistics from around the world and Saudi Arabia and identify the criticality in Saudi Arabia in particular. The results of this SLR conducted by Mohammad et al [9] strongly indicate that the healthcare sector needs a new and more robust data integrity approach.…”
Section: Related Workmentioning
confidence: 88%
“…The authors used here F.AHP.TOPSIS integrated technique for ranking the factors as discussed in Figure 2. 10,11 The authors have designed a hierarchy by the help of experts and applied the F.-AHP.TOPSIS on it.…”
Section: Fuzzy Ahp Topsismentioning
confidence: 99%
“…And evaluate the results of both methods and compare them with Fuzzy AHP.TOPSIS method. [10][11][12][13][14] They compared the results of the methods depicted in Figure 6. From the comparison, we observed that F.-AHP.TOPSIS generated better results than the Fuzzy Weighted Average and Classical AHP.TOPSIS method.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are the currency of the digital world and have become necessary for many disciplines to carry out day-to-day activities [ 2 ]. The use of technology and electronics worldwide has introduced an array of innovative and instrumental possibilities for scientists and researchers [ 3 ]. However, these possibilities have emerging risks.…”
Section: Introductionmentioning
confidence: 99%